Variations in the structure and function of the soil fungal communities in the traditional cropping systems from Madeira Island - Oliveira, Maria Cristina O.; Alves, Artur; Fidalgo, Cátia; de Freitas, José G. R.; Pinheiro de Carvalho, Miguel A. A. (Frontiers in Microbiology, 2024)
Agricultural soils are responsible for ecological functions and services that include primary production of food, fibre and fuel, nutrient cycling, carbon cycling and storage, water infiltration and purification, among others. Fungi are important drivers of most of those ecosystem services. Given the importance of fungi in agricultural soils, in this study, we aimed to characterize and analyse the changes of the soil fungal communities of three cropping systems from Madeira Island, where family farming is predominant, and investigate the response of fungi and its functional groups to soil physicochemical properties. To achieve that, we sequenced amplicons targeting the internal transcribed spacer 1 (ITS1) of the rRNA region, to analyse soil samples from 18 agrosystems: 6 vineyards (V), 6 banana plantations (B) and 6 vegetable plantations (H). Our results showed that alpha diversity indices of fungal communities are similar in the three cropping systems, but fungal composition and functional aspects varied among them, with more pronounced differences in B. Ascomycota, Basidiomycota and Mortierellomycota were the main phyla found in the three cropping systems. Agaricomycetes and Sordariomycetes are the predominant classes in B, representing 23.8% and 22.4%, respectively, while Sordariomycetes (27.9%) followed by Eurotiomycetes (12.3%) were the predominant classes in V and Sordariomycetes (39.2%) followed by Tremellomycetes (8.9%) in the H. Saprotrophs are the fungal group showing higher relative abundance in the three cropping systems, followed by plant pathogens. Regarding symbionts, endophytes were highly observed in B, while mycorrhizal fungi was predominant in V and H. The structure of fungal communities was mainly correlated with soil content of P, K, N, Fe and Cu. In addition, we identified bioindicators for each cropping system, which means that cultivated crops are also drivers of functional groups and the composition of communities. Overall, the three cropping systems favored diversity and growth of taxa that play important roles in soil, which highlights the importance of conservative management practices to maintain a healthy and resilient agrosystem.